1998
DOI: 10.1046/j.1440-1711.1998.00741.x
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of HLA class I antigen and ICAM‐2 on endothelial cells after in vitro infection with human cytomegalovirus

Abstract: Summary The aim of the present work is to investigate the expression of HLA class I antigen and intercellular adhesion molecule-2 (ICAM-2) on the surface of human umbilical cord endothelial cells (HUVEC) after infection with human cytomegalovirus (HCMV). The expression of HLA class I antigen and ICAM-2 were determined (using antibodies against HLA class I antigen and ICAM-2) by attachment inhibition assay and¯ow cytometric analysis. Attachment inhibition assay demonstrated that HCMV increased the expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Studies report that hCMV induces production of the EC proinflammatory mediators interleukin 8 (IL-8) (4,5) and IL-6 (6) and expression of the leukocyte adhesion receptor ICAM-1 (7,8). In addition, reports have shown that hCMV-infected EC (hCMV-EC) supported enhanced leukocyte recruitment (5,(9)(10)(11). These heavily cited studies, particularly those demonstrating a role for hCMV-induced IL-8 in neutrophil transmigration (4,5), support the idea that hCMV contributes to the development or exacerbation of inflammatory pathologies.…”
mentioning
confidence: 99%
“…Studies report that hCMV induces production of the EC proinflammatory mediators interleukin 8 (IL-8) (4,5) and IL-6 (6) and expression of the leukocyte adhesion receptor ICAM-1 (7,8). In addition, reports have shown that hCMV-infected EC (hCMV-EC) supported enhanced leukocyte recruitment (5,(9)(10)(11). These heavily cited studies, particularly those demonstrating a role for hCMV-induced IL-8 in neutrophil transmigration (4,5), support the idea that hCMV contributes to the development or exacerbation of inflammatory pathologies.…”
mentioning
confidence: 99%